Investigation on the Optimum Cement–Slag Artificial Aggregates at Different CO2 Curing Regime - Abila Hena Anayet,; Nur Hafizah Abd Khalid,; Nurdalina Syuhada Zulkifli,; Siti Aishah Jupri,; Md Sajid Alam,; Mohamad Haqzim Ayob,; Nor Hafizah Berahim,; Hazratul Mumtaz Lahuri,; Farahdila Kadirkhan, (International Journal of Integrated Engineering, 2025)
Carbon dioxide (CO2) capturing is an attractive approach for producing low carbon construction materials such as artificial aggregates. Therefore, this paper investigates the optimization of cement–slag artificial aggregates under different CO2 curing regimes. The mix proportion used is 50% Ground Granulated Blast Furnace Slag (GGBS) and 50% Ordinary Portland Cement (OPC) with 20% of water under various curing conditions. The curing regimes include CO2 curing followed by water and air curing at different curing ages: 1 day of CO2 curing followed by 27 days of water and air curing, 2 days of CO2 curing followed by 26 days of water and air curing, and 3 days of CO2 curing water 25 days of water and air curing; with 28 days of total curing, respectively. After through curing process, several tests were carried out on cement–slag artificial aggregates including an individual strength test, aggregate crushing value test, visual carbonation by phenolphthalein solution and CO2 uptake by thermogravimetric analysis test. These tests provide a thorough assessment of the artificial aggregates by examining their strength and chemical characteristics under various curing conditions. The results indicated that 3 days of CO2 curing followed by 25 days of air curing is optimal, showing 6.71 MPa of individual crushing strength and 18.56% of aggregate crushing value. Thermogravimetric analysis indicated that calcium hydroxide (Ca(OH)2) played a significant role in synthesizing calcium silicate hydrate (C–S–H) gel, contributing to aggregate strength. The carbonation of Ca(OH)2 to calcium carbonate (CaCO3) enhanced aggregate durability by reducing permeability and increasing material density. The findings show that the optimal curing regime produces the best results in terms of strength and CO2-capturing properties, which was the main goal of this study.